Evaluation of crop structure optimization policy quantitatively and future directions in China: a PMC-Index model approach - Su, Ruiqing; Sui, Hongjun; Ren, Gaofeng; Wang, Quanxi (Frontiers in Sustainable Food Systems, 2024)
Developing policies to optimize the planting structure is essential to ensure an adequate supply of agricultural products and guarantee food security. However, the rationality and comprehensiveness of China’s cropping structure optimization policies require scientific evaluation. Therefore, this research established an evaluation index system for China’s planting structure optimization policies using text mining and the PMC-Index model to evaluate eight agricultural cropping structure optimization policies in China since 2003. The results showed that: (1) The PMC-Index showed a general upward trend across the eight policies, with scores ranging from 4.88 to 6.61. (2) Seven of the eight policies were deemed acceptable, while one was classified as low. (3) The Chinese government has long focused on optimizing the structure of agricultural cultivation, and relevant policies have made significant progress in terms of logical connotation and long-term feasibility. However, there is still room for improvement in enhancing regulatory effectiveness and strengthening interdepartmental collaboration. It is recommended that the government develop more flexible and diverse incentive mechanisms, strengthen interdepartmental coordination, expand policy coverage, enhance the comprehensiveness of policy functions, and elevate support for agricultural technology.